Pharmacokinetics and Pharmacodynamics of Esomezol DR, a New Dual Delayed-Release Formulation of Esomeprazole 20 Mg or 40 Mg, in Healthy Subjects - Kim HC; Yang E; Ban MS; Kim YK; Hong SH; Jung J; Jang IJ; Lee S (Dove Medical Press, 2023)
Hyun Chul Kim,1,2 Eunsol Yang,1,3 Mu Seong Ban,1 Yu Kyong Kim,4 Sung Hee Hong,5 Jina Jung,5 In-Jin Jang,1 SeungHwan Lee1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Integrated Major in Innovative Medical Science, Seoul National University Graduate School, Seoul, Republic of Korea; 3Kidney Research Institute, Seoul National University Medical Research Center, Seoul, Republic of Korea; 4Department of Clinical Pharmacology and Therapeutics, Chungbuk National University College of Medicine and Hospital, Cheongju, Republic of Korea; 5Hanmi Pharmaceutical Co., Ltd., Seoul, Republic of KoreaCorrespondence: SeungHwan Lee, Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea, Tel +82-2-2072-2343, Fax +82-2-742-9252, Email leejh413@snu.ac.krBackground: Esomeprazole, a proton pump inhibitor (PPI), is widely used to treat acid-related disorders, but it has short plasma half-life which can cause insufficient gastric acid suppression, such as nocturnal acid breakthrough. A new dual delayed-release (DR) formulation of esomeprazole (Esomezol DR), was developed to extend the duration of gastric acid suppression.Purpose: This study aimed to evaluate the pharmacokinetics (PKs) and pharmacodynamics (PDs) of esomeprazole for the DR formulation compared to a conventional enteric-coated (EC) formulation (Nexium) in healthy male subjects.Methods: Two randomized, open-label, multiple-dose, two-way crossover studies with esomeprazole 20 mg and 40 mg were conducted. Subjects received the DR formulation or the EC formulation once daily for 7 days in each period with a 7-day washout. Serial blood samples were collected up to 24 hours after the 1st dose, and 24-hour intragastric pH was continuously monitored before the 1st dose as baseline and after the 1st and the 7th dose.Results: In 20 mg and 40 mg dose groups, 38 and 44 subjects completed the study, respectively. The DR formulation exhibited the dual-release pattern of esomeprazole, resulting in more sustained plasma concentration-time profiles compared to the EC formulation. The systemic exposure of esomeprazole for the DR formulation was comparable to that for the EC formulation, showing the similar area under the plasma concentration-time curve. The 24-hour gastric acid suppression was also similar between the two formulations, while the inhibition during night-time (22:00- 06:00) showed a better tendency in the DR formulation.Conclusion: The sustained exposure of esomeprazole in the DR formulation led to well-maintained and higher acid inhibition compared to the EC formulation, especially during the night-time. These results suggest that the DR formulation can be an alternative formulation to the conventional EC formulation, expecting the potential of relieving nocturnal acid-related symptoms.Keywords: proton pump inhibitors, esomeprazole, dual delayed-release formulation, gastro-esophageal reflux disease, GERD, nocturnal acid breakthrough